2018
DOI: 10.3390/coatings8050187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lamellar Interface Morphology on Cracking Resistance of Plasma-Sprayed YSZ Coatings

Abstract: Splat morphology is an important factor that influences the mechanical properties and durability of thermal barrier coatings (TBCs). In this study, yttria-stabilized zirconia (YSZ) coatings with different lamellar interface morphologies were deposited by atmospheric plasma spraying (APS) using feedstocks with different particle sizes. The influence of lamellar interface roughness on the cracking resistance of the coatings was investigated. Furthermore, the thermal shock and erosion resistance of coatings depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…It was found that the interfacial roughness has a significant effect on the surface roughness, interfacial stress distribution, and propagation modes of cracks. Sfar et al [61] established a TBCs failure model, the residual stress of the TC region at the peak of TC/TGO interface due to thermal mismatch failure was studied, which was used to evaluate the interface toughness or to measure the initiation of cracks. The stress concentration near the TGO layer was discussed when the vertical crack was above the peak value of the TGO layer by establishing the TBCs failure model.…”
Section: Thermal Expansion Mismatchmentioning
confidence: 99%
“…It was found that the interfacial roughness has a significant effect on the surface roughness, interfacial stress distribution, and propagation modes of cracks. Sfar et al [61] established a TBCs failure model, the residual stress of the TC region at the peak of TC/TGO interface due to thermal mismatch failure was studied, which was used to evaluate the interface toughness or to measure the initiation of cracks. The stress concentration near the TGO layer was discussed when the vertical crack was above the peak value of the TGO layer by establishing the TBCs failure model.…”
Section: Thermal Expansion Mismatchmentioning
confidence: 99%
“…The parameter measurement and formula derivation are complex and inefficient. Jing et al [13] proposed a TBC life prediction model based on the nonlinear accumulation of oxidative damage and cyclic damage and reported that the error between the damage prediction and test result does not exceed ±10%. Jiang et al [14] studied the initiation and propagation of cracks at the TBC interface and ceramic layer by cohesive elements and extended finite-element methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that improving strain tolerance of the ceramic topcoat via the microstructure and composition can dramatically improve the durability of TBCs. Presently, the typical microstructure of the YSZ coating that experts focus on are quasi-columnar YSZ coatings prepared by plasma-sprayed physical-vapor deposition (PS-PVD) [26][27][28][29][30] or suspension plasma spraying (SPS) [31,32]; columnar YSZ coating deposited by electron-beam physical-vapor deposition (EB-PVD) [33][34][35]; segmentation cracks in ceramic topcoat [36,37], the double-layer structure of ceramic coatings [38], and self-enhancing ceramic coating [39].…”
Section: Introductionmentioning
confidence: 99%